Instructional Theory and Technology for the New Paradigm of Education - Charles M. Reigeluth (Universidad de Murcia, 2012)
This article describes instructional theory that supports post-industrial education and training systems - ones that are customized and learner-centered, in which student progress is based on learning rather than time. The article describes universal methods of instruction, situational methods, core ideas of the post-industrial paradigm of instruction, the importance of and problems with task-based instruction, a vision of an instructional theory for post-industrial education and training, and the roles that may be played by the teacher, the learner, and technology in the new paradigm.